2011
DOI: 10.1101/lm.2023011
|View full text |Cite
|
Sign up to set email alerts
|

Neural circuitry and plasticity mechanisms underlying delay eyeblink conditioning

Abstract: Pavlovian eyeblink conditioning has been used extensively as a model system for examining the neural mechanisms underlying associative learning. Delay eyeblink conditioning depends on the intermediate cerebellum ipsilateral to the conditioned eye. Evidence favors a two-site plasticity model within the cerebellum with long-term depression of parallel fiber synapses on Purkinje cells and long-term potentiation of mossy fiber synapses on neurons in the anterior interpositus nucleus. Conditioned stimulus and uncon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
166
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 177 publications
(177 citation statements)
references
References 201 publications
(237 reference statements)
7
166
0
4
Order By: Relevance
“…4B, 5B). This pattern of a decrease in activity preceded by an increase has been observed before in recordings from paralyzed animals (Hesslow and Ivarsson, 1994) and is generally consistent with the previously proposed role of PCs in response timing (Mauk and Donegan, 1997;Medina and Mauk, 2000), and a role for rebound excitation in the deep nucleus neurons in response expression (Freeman and Steinmetz, 2011). For all four ISIs the cross-correlation analyses revealed that eyelid PC activity was poorly related to subsequent eyelid acceleration but was about equally well related to subsequent eyelid position and velocity (Figs.…”
Section: Eyelid Pc Responses During Training At Four Isissupporting
confidence: 69%
“…4B, 5B). This pattern of a decrease in activity preceded by an increase has been observed before in recordings from paralyzed animals (Hesslow and Ivarsson, 1994) and is generally consistent with the previously proposed role of PCs in response timing (Mauk and Donegan, 1997;Medina and Mauk, 2000), and a role for rebound excitation in the deep nucleus neurons in response expression (Freeman and Steinmetz, 2011). For all four ISIs the cross-correlation analyses revealed that eyelid PC activity was poorly related to subsequent eyelid acceleration but was about equally well related to subsequent eyelid position and velocity (Figs.…”
Section: Eyelid Pc Responses During Training At Four Isissupporting
confidence: 69%
“…The acoustic CS signal is relayed through the medial thalamic nuclei, the cochlear nucleus, the nucleus of the lateral lemniscus, and finally to the PN, the last precerebellar nucleus that conveys acoustic signals to the cerebellum (Freeman & Steinmetz, 2011). Auditory cues were previously reported to be selectively relayed to the cerebellum through the LPN (Bao, Chen, & Thompson, 2000;Steinmetz et al, 1987), while other research found auditory-evoked responses throughout both the LPN and MPN (Cartford, Gohl, Singson, & Lavond, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For example, learning to fear specific stimuli or events depends on the amygdala (Duvarci & Pare, 2014;LeDoux, 2014), whereas simple forms of sensorimotor learning, such as eyeblink classical conditioning, depend on the cerebellum and brainstem (Christian & Thompson, 2003;Freeman & Steinmetz, 2011). In delay eyeblink conditioning (EBC), a light or tone conditioned stimulus (CS) is repeatedly paired with a mildly aversive corneal air puff or periorbital shock unconditioned stimulus (US).…”
mentioning
confidence: 99%
“…Decades of research have established that the cerebellum is essential for the acquisition and retention of eyeblink conditioning (for review, see Freeman and Steinmetz 2011). The cerebellum receives conditioned stimulus (CS) information from the pontine nuclei via the middle cerebellar peduncle (MCP) (Steinmetz et al , 1987Steinmetz 1990), and unconditioned stimulus (US) information is transmitted to the cerebellum via climbing fiber projections from the inferior olive (McCormick et al 1985;Mauk et al 1986).…”
mentioning
confidence: 99%